Do fast food restaurants surrounding schools affect childhood obesity? - Asirvatham, Jebaraj (Econ Hum Biol, 2019)
In this study, we estimate the effect of fast food environment surrounding schools on childhood body mass index (BMI). We use two methods that arrive at a similar conclusion, but with different implications. Using school distance from the nearest federal highway to instrument for restaurant location, we find the surrounding restaurants to only marginally affect a student’s BMI measure. The effect size also decreases with increasing radial distances from school, 0.016 standard deviations at one-third of a mile and 0.0032 standard deviations at a mile radial distance. This indicates the decreasing influence of restaurants on a child’s BMI as its distance from school increases. On a subset of students who were exogenously assigned to different school food environment, we find no effect of the fast food restaurants. An important contextual aspect is that nearly all schools in this sample observed closed campus policy, which does not allow students to leave campus during lunch hours.